THE MEANING OF PANCASILA IN SUFISTIC PSYCHOLOGICAL PERSPECTIVE - Zainur Rakhman, Muhammad (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2018)
Pancasila has many functions for Indonesia; as the foundation of the state philosophy, the source of all law sources, nation’s view of life, as well as the soul and personality of Indonesia. Pancasila has not become a common value that is the basic for every remark and behavior. Because of that Pancasila needs to be interpreted in useful point of view to build personality with deep contemplation of it. One of the signification is on Sufistic Psychology’s Perspective. Sufistic Psychology as the development of Psychology based on Tasawuf, can be a useful perspective in interpreting Pancasila. Psycho-Sufistik that oriented in moral-transcendental can provide a deep and focused meaning to Pancasila. This research use a qualitative methodology, which elaborates the meaning of Pancasila in Sufistic Psychology’s perspective. Before Pancasila was elaborated in Sufistic Psychology’s perspective, the meaning of Pancasila was analyzed using semiotics. This study aims to interpret Pancasila in Sufistic Psychology’s perspective.The results of the study shows that the research is useful to enrich the intellectual treasures of Pancasila